2015
DOI: 10.3386/w20932
|View full text |Cite
|
Sign up to set email alerts
|

Veterans’ Labor Force Participation: What Role Does the VA’s Disability Compensation Program Play?

Abstract: The authors thank Erzo F. P. Luttmer, Elizabeth Bass, Heidi Golding, and seminar participants at the ASSA meetings, the Federal Reserve Board of Governors, and Stanford University for helpful comments. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Johnson et al (2016) examine military service transmission within the Minnesota Twin study and find directionally similar effects (albeit an order of magnitude larger). 14 See, for example, Angrist (1990); Dobkin and Shabani (2009);Angrist, Chen, and Frandsen (2010) ;Duggan, Rosenheck, and Singleton (2010); Angrist and Chen (2011);Angrist, Chen, and Song, (2011);Autor, Duggan, and Lyle (2011);Lindo and Stoecker (2014); Coile, Duggan, and Guo (2015); and Autor, Duggan, Greenberg, and Lyle (2015).…”
mentioning
confidence: 99%
“…Johnson et al (2016) examine military service transmission within the Minnesota Twin study and find directionally similar effects (albeit an order of magnitude larger). 14 See, for example, Angrist (1990); Dobkin and Shabani (2009);Angrist, Chen, and Frandsen (2010) ;Duggan, Rosenheck, and Singleton (2010); Angrist and Chen (2011);Angrist, Chen, and Song, (2011);Autor, Duggan, and Lyle (2011);Lindo and Stoecker (2014); Coile, Duggan, and Guo (2015); and Autor, Duggan, Greenberg, and Lyle (2015).…”
mentioning
confidence: 99%
“…6 A 2015 analysis found that veterans' labor force participation declined over the previous 35 years in close correlation with growth in service-connected disability. 7 Without effective intervention, the growing numbers of unemployed prime working-aged individuals with disabling PTSD could have a substantial economic impact for generations to come.…”
mentioning
confidence: 99%
“…See, for example, Angrist (1990); Dobkin and Shabani (2009);Angrist, Chen, and Frandsen (2010) ;Duggan, Rosenheck, and Singleton (2010); Angrist and Chen (2011);Angrist, Chen, and Song, (2011);Autor, Duggan, and Lyle (2011);Lindo and Stoecker (2014); Coile, Duggan, and Guo (2015); and Autor, Duggan, Greenberg, and Lyle (2015). Parental inputs have traditionally been linked to children's outcomes (e.g., Becker and Tomes, 1976, 1979, and 1986Becker, 1981;Cunha, Heckman, and Schennach, 2010).…”
mentioning
confidence: 99%